The genus Phagocata Leidy (Platyhelminthes, Tricladida) in Israel, a new species of Phagocata from Lake Kinneret, and an emended description of Dugesia salina - Bromley-Schnur, Heather J. (Zootaxa, 2021)
The genus Phagocata (Platyhelminthes, Tricladida) is represented in Israel by two pigmented species, namely, Phagocata armeniaca (Komárek, 1916), reported previously from Armenia, the Caucasus and eastern Turkey, and more recently known from the constantly cold headwaters of the River Jordan in northern Israel, and Phagocata punctata sp. nov., which was found inhabiting the littoral of the south-eastern shore of Lake Kinneret where there are large seasonal temperature fluctuations. Several samples of both species were collected in different seasons and raised in the laboratory at various temperatures and their habitats, morphology, karyology (2n = 34) and breeding behaviour were compared. The results of cross-breeding experiments are given, with most of the F1 offspring showing a range of patterns of colouration, gut branching and fecundity which were intermediate to those of the parent species. However, crossbreeding also resulted in a small proportion of abnormalities among the F1, and especially the F2, generations, indicating an incomplete reproductive compatibility, but supporting the hypothesis of their common origin. An emended description of Dugesia salina (Whitehouse, 1914), is also given together with karyological data (2n = 16) from material collected from a saline spring, En Sheva (Tabgha), situated on the north-western shore of Lake Kinneret.